Genetic variants in human BCL2L11 (BIM) are associated with ulcerative forms of Buruli ulcer - João Fevereiro; Alexandra G. Fraga; Carlos Capela; Ghislain E. Sopoh; Ange Dossou; Gilbert Adjimon Ayelo; Maria João Peixoto; Cristina Cunha; Agostinho Carvalho; Fernando Rodrigues; Jorge Pedrosa (Emerging Microbes and Infections)
Buruli ulcer (BU) is a devastating skin mycobacterial infection characterized by extensive cell death, which was previously suggested to be mediated by Bcl2-like protein 11 (BIM, encoded by the BCL2L11 gene). We here report the association of genetic variants in BCL2L11 with ulcerative forms of the disease in a cohort of 618 Beninese individuals. Our results show that regulation of apoptosis in humans contributes to BU lesions associated with worse prognosis, prompting for further investigation on the implementation of novel methods for earlier identification of at-risk patients.